Precarity and Resilience: An Ecofeminist Reading of the African Child in Fiction by Contemporary Women Writers - Shiyoka, Selma Kauna (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.